2021
DOI: 10.1590/1809-4430-eng.agric.v41n6p591-598/2021
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Rectal Temperature of Goats Based on Surface Temperature

Abstract: Infrared thermography (IR) is a non-invasive tool with potential to indicate changes in the animal's thermal conditions in response to the thermally stressful environment. The objective of this study was to evaluate the application of IR to estimate the rectal temperature of crossbred goats of the Boer breed. Six male crossbred goats of the Boer breed were distributed in a completely randomized design and submitted to temperatures of 26, 30 and 34 °C. Rectal temperature (RT) and thermograms data were collected… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Due to this, IRT can detect these vasomotor changes [96,97]. A study carried out by Marques et al [14] evaluated the potential of IRT as a tool to assess thermal changes in six male Boer crossbred goats exposed to three different temperatures of 26, 30, and 34 • C. By assessing the surface temperature of the ocular region, head, shoulder, and hindlimbs, the authors observed that the surface temperature of all regions significantly increased by 2 • C after exposure to the highest temperature. Moreover, it was also observed that the ocular temperature was positively correlated with the rectal temperature of the animals (r = 0.95).…”
Section: Infrared Thermography As a Tool To Assess Thermostability In...mentioning
confidence: 99%
See 2 more Smart Citations
“…Due to this, IRT can detect these vasomotor changes [96,97]. A study carried out by Marques et al [14] evaluated the potential of IRT as a tool to assess thermal changes in six male Boer crossbred goats exposed to three different temperatures of 26, 30, and 34 • C. By assessing the surface temperature of the ocular region, head, shoulder, and hindlimbs, the authors observed that the surface temperature of all regions significantly increased by 2 • C after exposure to the highest temperature. Moreover, it was also observed that the ocular temperature was positively correlated with the rectal temperature of the animals (r = 0.95).…”
Section: Infrared Thermography As a Tool To Assess Thermostability In...mentioning
confidence: 99%
“…However, it is essential to establish which thermal window could be more suitable to show sympathetic activity after HS [99,100]. One of the most used thermal windows to find associations with rectal temperature is the ocular region [14,15,98]. This anatomical region, in particular, the lacrimal caruncle blood supply from the infraorbital artery, is a region highly sensible to vasomotor changes [9].…”
Section: Infrared Thermography As a Tool To Assess Thermostability In...mentioning
confidence: 99%
See 1 more Smart Citation
“…an experimenter guiding animals loudly with exaggerated arm movements to a nearby pen (Bartolomé et al 2019). As eye temperature correlates strongly with core temperature in goats (Marques et al 2021), we may expect eye and core temperature to increase in tandem with decreases in temperature of other regions, such as the muzzle (e.g. Proctor and Carder 2016).…”
Section: Thermal Imagingmentioning
confidence: 99%
“…However, the use of this technology also suffers from several disadvantages that must be carefully considered before it can be effectively applied in practice. For example, skin temperature is affected by numerous endogenous factors, such as individual, breed, sex and physical activity (also affects cardiac measures; Jansson et al 2021, Travain andValsecchi 2021), as well as environmental variables, such as ambient temperature, humidity and wind intensity, which influence peripheral temperatures both directly and through homeostatic processes (Marques et al 2021, Jansson et al 2021. Further extraneous variables that influence the accuracy of peripheral temperature readings include distance or angle of the subject to the camera (Tattersall 2016, Ijichi et al 2020, the ROI chosen, its size and the specific measure used (i.e.…”
Section: Thermal Imagingmentioning
confidence: 99%